Honor System: An Empirical Analysis - AHMED, Rukhsar; DIN, Imam ud (Asian Journal of Empirical Research, 2013)
Honor system is an honest way of running the system according to the rules and regulations in the manner that nobody could break the trust. The offences committed under the honor system include; honor killing, plagiarism, absconding of people from home, telling lie and forced marriage under honor system, man is a head of a family who has to defend his family’s honor. Woman is an asset of the family, who decides the fate of his daughter and sister including forced marriage and in case of her refusal; he is al liberty to kill her in the name of family honor. Customary traditions, jirgas are empowered to decide the cases including honor killing. Although so many countries of the World are reportedly involved in so called honor killings, but the Muslim countries are known as main specially, Pakistan is one of the dangerous countries with reference to honor killing. Although, there is no concept of honor killing in Islam. Yet this heinous crime is Islam and Muslims being related to Islam & Muslims by the Western media, Islamic laws strictly prohibit any killing which is unjustifiable. Efforts made by the government failed due to existence of jirgas representing tribal system which needs to be done away with by creating awareness and effective education to the people so as to know their rights, duties and responsibilities. In this regard, Islamic teachings play an important role.